Learning from Greensboro: truth and reconciliation in the United States - Magarrell, Lisa (Pennsylvania studies in human rights)
The truth about greensboro -- Remembering victims and survivors -- Individual truths -- The truth commission idea -- Building the framework -- Seating the commission -- Starting up, establishing independence -- Research and the complexity of truth -- Engaging the public -- The report -- Next steps and response -- The project and the commission -- The media and official Greensboro -- Opposition and critiques -- Interest and support from outside -- Lessons from the process -- An early assessment -- Comparing Greensboro -- Greensboro's legacy